Comprehensive cross‐platform comparison of methods for non‐invasive EGFR mutation testing: results of the RING observational trial. Issue 1 (13th November 2020) - Romero, Atocha; Jantus‐Lewintre, Eloisa; García‐Peláez, Beatriz; Royuela, Ana; Insa, Amelia; Cruz, Patricia; Collazo, Ana; Pérez Altozano, Javier; Vidal, Oscar Juan; Diz, Pilar; Cobo, Manuel; Hernández, Berta; et al.
Abstract : Several platforms for noninvasive EGFR testing are currently used in the clinical setting with sensitivities ranging from 30% to 100%. Prospective studies evaluating agreement and sources for discordant results remain lacking. Herein, seven methodologies including two next‐generation sequencing (NGS)‐based methods, three high‐sensitivity PCR‐based platforms, and two FDA‐approved methods were compared using 72 plasma samples, from EGFR ‐mutant non‐small‐cell lung cancer (NSCLC) patients progressing on a first‐line tyrosine kinase inhibitor (TKI). NGS platforms as well as high‐sensitivity PCR‐based methodologies showed excellent agreement for EGFR‐sensitizing mutations ( K  = 0.80–0.89) and substantial agreement for T790M testing ( K  = 0.77 and 0.68, respectively). Mutant allele frequencies (MAFs) obtained by different quantitative methods showed an excellent reproducibility (intraclass correlation coefficients 0.86–0.98). Among other technical factors, discordant calls mostly occurred at mutant allele frequencies (MAFs) ≤ 0.5%. Agreement significantly improved when discarding samples with MAF ≤ 0.5%. EGFR mutations were detected at significantly lower MAFs in patients with brain metastases, suggesting that these patients risk for a false‐positive result. Our results support the use of liquid biopsies for noninvasive EGFR testing and highlight the need to systematically report MAFs. Abstract : Plasma samples from 72 EGFR ‐mutant advanced NSCLC patients, collected upon progression to first‐line TKI, were analyzed by seven methodologies (two NGS‐based methods, three high‐sensitivity PCR‐based platforms, and two FDA‐approved methods). Our study demonstrates a good to excellent agreement between methodologies and supports the use of liquid biopsies for therapy decision‐making.